The Effect of Katuk Leaf Extract (Sauropus androgynus (L.) Merr.) Administration on the Libido of Male White Rats (Sprague Dawley) - Watsiqoh Anisti Harahap; Huwainan Nisa Nasution (Universitas Muhammadiyah Palembang, 2026)
ABSTRACT Low libido is one of the most common forms of sexual dysfunction among adult men and has a relatively high prevalence, including in Indonesia. The increasing public interest in herbal medicine has encouraged the use of katuk leaves (Sauropus androgynus (L.) Merr), which contain bioactive compounds such as saponins, alkaloids, and flavonoids that are presumed to possess aphrodisiac properties. This study aimed to evaluate the effect of katuk leaf extract on libido enhancement in male white rats. This study employed a true experimental design using a post-test with control group approach. The animals were divided into three groups, namely a negative control group receiving distilled water and standard feed, and two treatment groups receiving katuk leaf extract at doses of 100 mg/kgBW and 200 mg/kgBW, respectively. The extract was obtained through maceration using 96% ethanol. The observed parameters were the frequencies of introduction and climbing as indicators of libido-related behaviour. The analysis showed no statistically significant differences among the groups for the introduction parameter (p = 0.310) and the climbing parameter (p = 0.368). These findings indicate that administration of katuk leaf extract for 7 days did not significantly enhance libido. This outcome may have been influenced by several factors, including the absence of estrous phase screening in female rats, excessive cage lighting, and a possible reduction in bioactive compound content due to a suboptimal drying process. Previous studies reporting significant effects generally used longer treatment durations and stricter control of physiological conditions. Keywords: Aphrodisiac, Libido, Sauropus androgynus (L.) Merr.